2014
DOI: 10.4236/aar.2014.35045
|View full text |Cite
|
Sign up to set email alerts
|

Real and Perceived Physical Functioning in Italian Elderly Population: Associations with BADL and IADL

Abstract: This study aimed to identify the key physical abilities (aerobic endurance, gait speed, balance, strength) and psychological variables associated with the level of basic (BADL) and instrumental (IADL) activities of daily living in an autonomous community-dwelling elderly population in Italy. 135 elderly people (63% women; mean age = 73.3, SD = 5.5) were included in the study. Stepwise regression was performed to verify the association between these variables and the level of BADL and IADL in the elderly partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…It has been shown that the ability to perform BADL is the most important factor when assessing the quality of life of those with dementia [58]. An individual's quality of life is closely linked with their motivation to engage with physical activity [25,58] and thereby their ability to remain mobile and continue performing BADL autonomously [59,60]. Through enabling physical activity in care homes, this cycle can be maintained, leading to positive mental and physical benefits for residents.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the ability to perform BADL is the most important factor when assessing the quality of life of those with dementia [58]. An individual's quality of life is closely linked with their motivation to engage with physical activity [25,58] and thereby their ability to remain mobile and continue performing BADL autonomously [59,60]. Through enabling physical activity in care homes, this cycle can be maintained, leading to positive mental and physical benefits for residents.…”
Section: Discussionmentioning
confidence: 99%